Tax induces nuclear translocation of NF-kappa B through dissociation of cytoplasmic complexes containing p105 or p100 but does not induce degradation of I kappa B alpha/MAD3 - Eduardo Muñóz; Gilles Courtois; Philippe Veschambre; Pierre Jalinot; Alain Israël (1994)
The activity of the NF-kappa B transcription factor is controlled through cytoplasmic retention by either of two types of molecules: the inhibitor I kappa B alpha/MAD3 or the p105 and p100 precursors of the p50 and p52 DNA-binding subunits. Treatment of cells with classical NF-kappa B inducers such as tumor necrosis factor, interleukin-1, phorbol myristate acetate, and lipopolysaccharide results in MAD3 degradation followed by nuclear translocation of NF-kappa B. On the other hand, the mechanisms involved in the dissociation of the cytoplasmic p105/p100-containing complexes are largely unknown. The Tax protein encoded by human T-cell leukemia virus type 1 is a potent activator of viral and cellular gene transcription. It does not bind DNA directly but seems to activate transcription indirectly either by enhancing the activities of the transcription factors that recognize responsive elements located in the promoters of the Tax-responsive genes or by forming ternary complexes with these factors and DNA. It has been previously shown that Tax is able to induce nuclear translocation of NF-kappa B. We demonstrate here that Tax can induce translocation of members of the NF-kappa B family retained in the cytoplasm through their interaction with either p105 or p100. On the other hand, Tax induces no apparent degradation of MAD3, although experiments using cycloheximide indicate that it decreases the half-life of MAD3. However, this activity is shared by a mutant of Tax which is unable to activate NF-kappa B. These results suggest that Tax activates NF-kappa B essentially through the p105/p100 retention pathway.